1999
DOI: 10.1902/jop.1999.70.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Destructive Periodontal Disease in Adults 30 Years of Age and Older in the United States, 1988‐1994

Abstract: Periodontitis is prevalent in the U.S. adult population. The results show that black and Mexican American males have poorer periodontal health than the rest of the U.S. adult population. Primary and secondary preventive measures should therefore be specifically targeted towards these groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

50
597
9
30

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 661 publications
(686 citation statements)
references
References 14 publications
50
597
9
30
Order By: Relevance
“…Periodontal diseases, among the most common infectious diseases in the world today, are characterized by the destruction of several tissues surrounding the tooth, including alveolar bone, cementum, and the periodontal ligament [1]. A challenge in periodontal therapy is to promote the regeneration of these tooth-supporting structures.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal diseases, among the most common infectious diseases in the world today, are characterized by the destruction of several tissues surrounding the tooth, including alveolar bone, cementum, and the periodontal ligament [1]. A challenge in periodontal therapy is to promote the regeneration of these tooth-supporting structures.…”
Section: Introductionmentioning
confidence: 99%
“…If left untreated, chronic periodontitis (CP) can lead to serious problems such as tooth loss. Indeed, periodontal disease is the number one cause of tooth loss in the United States, accounting for half of all tooth loss in U.S. adults (1). There is considerable evidence that the clinical impact of periodontal disease extends beyond the oral cavity (2).…”
mentioning
confidence: 99%
“…In addition, the Kappa value ranged from 0.8 to 1.0 for PD and 0.7 to 1.0 for CAL. The National Health and Nutrition Examination Survey (NHANES) III [14] found that about 30.0% of 70-to 80-year-old subjects had moderate to advanced periodontitis. Accordingly, we used the 30th percentile to indicate a poor periodontal condition.…”
Section: Oral Examinationsmentioning
confidence: 99%